Relationship Between Conventional Medicine Chapters in ICD-10 and Kampo Pattern Diagnosis: A Cross-Sectional Study - Wu, Xuefeng; Le, Thomas K.; Maeda-Minami, Ayako; Yoshino, Tetsuhiro; Horiba, Yuko; Mimura, Masaru; Watanabe, Kenji (Frontiers in Pharmacology, 2021)
Objectives: The newest revision to the International Classification of Diseases, the 11th edition (ICD-11) includes disease classifications from Asian medicine, including Kampo medicine. These disease classifications allow for comparisons between disease classifications from conventional medicine and traditional Japanese medicine. Design/Location/Subjects/Interventions: This is an exploratory, cross-sectional study exploring the relationship between conventional medicine diagnoses and traditional Japanese medicine diagnoses at a large Kampo clinic in Japan. Patients were seen from October 1st, 2014 to June 30th, 2019 and were 20 years of age or older. Outcome measures: Patients presented with one or more conventional medicine ICD-10 codes into the clinic and were given one descriptor from the ICD-11 within the heat-cold module, excess-deficiency module, and an optional body constituents module. The distribution of these traditional Japanese medicine codes was examined in relation to conventional medicine chapters. Results: 1209 patients were included in our final analysis. Patient number, ages, sex ratio and BMI varied within conventional medicine ICD-10 chapters and traditional Japanese medicine descriptor codes. Certain conventional medicine chapters are related to specific traditional Japanese medicine descriptor codes, such as chapter IV (endocrine, nutritional and metabolic diseases) with excess, heat, and kidney qi deficiency. Conclusion: The advent of the ICD-11 allows for systematic, standardized comparisons between traditional Japanese medicine and contemporary medicine. In this exploratory study, our findings support the independence of traditional Japanese medicine pattern descriptors with ICD-10 conventional medicine chapters. Code overrepresentations in relation to conventional medicine diseases and by age and sex should be an area of future investigation to best understand how to synergize and improve patient care.